The application of EU competition law in the European natural gas market - Bilgi, Hande (My University, 2019)
Bu tezin amacı Avrupa Birliği (“AB”) Rekabet Hukuku kurallarının AB doğalgaz marketinde (“market”) nasıl uygulandığının incelenmesidir. Marketin inceleme alanı olarak seçilme sebebi, bu alanın liberalizasyon sürecinden önce AB üye devletlerin ulusal sorunu olarak görülmesi ile doğalgaz kaynaklarının tekeller tarafından işletilmesi ve konunun AB seviyesinde ele alınmamasıdır. Ayrıca marketin ithal doğalgaza ve altyapı tesislerine, örneğin doğalgaz boru hattı ve doğalgaz depolama ünitelerine erişime bağlı olması ve bu bağlılığın rekabet açısından market koşullarını belirlemesi de tez konusunun seçiminde etken olmuştur.İnceleme, marketteki gelişmelerin ve liberalizasyon sürecinin değerlendirilmesi ve AB Komisyon soruşturmaları ile AB Adalet Divanı’nın verdiği kararlar ışığında gerçekleştirilecektir. Doğalgaz anlaşmalarının özellikleri ve doğalgaz marketindeki iştiraklerin hâkim durumu AB İşleyişi Hakkında Anlaşma’nın 101. ve 102. maddeleri kapsamında analiz edilecek ve ayrıca markette planlanan birleşme işlemleri de AB Birleşme Regülasyonu kapsamında ele alınacaktır.

The purpose of this thesis is to examine the application of European Union (“EU”) competition law to the EU natural gas market (“market”). The market was chosen as an examination area due to the fact that it was a national issue for the Member States and the natural gas resources were operated by the monopolies and was not handled at the EU level beforehand of the liberalisation procedure. Moreover the market depends on imported natural gas as well as infrastructures such as gas pipelines and gas storage facilities, thus these dependencies affect the market pattern in terms of competition. Examination shall be conducted by evaluating the developments in the market and its liberalisation process as well as reviewing the investigation of the European Commission and decisions of the Court of Justice of the EU (“CJEU”). Mainly, the characteristics of the natural gas agreements and dominant position of the undertakings operating in the natural gas market shall be analysed under Article 101 and Article 102 of the Treaty of the Functioning of the EU (“TFEU”) and also the proposed concentration in the market shall be assessed under the EU Merger Regulation.
Keywords: AB Enerji Hukuku; AB Rekabet Hukuku EU Energy Law; Avrupa Birliği; Avrupa Doğalgaz Piyasası; EU Competition Law; EU Natural Gas Market; European Union; Hukuk; Law